2021
DOI: 10.1097/adm.0000000000000883
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the Power of Social Media to Understand the Impact of COVID-19 on People Who Use Drugs During Lockdown and Social Distancing

Abstract: Objectives:This paper uses a social media platform, Reddit, to identify real-time experiences of people who use drugs during the COVID-19 lock-down.Methods:Reddit is a popular and growing social media platform, providing a large, publicly available dataset necessary for high performance of machine learning and topic modeling techniques. We used opioid-related “subreddits,” communities where Reddit users engage in conversations about drug use, to examine COVID-19-related content of posts and comments from March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…40,42 The review shows that, as a result of such frustrations, some individuals felt they had to self-manage withdrawal or reported that they wished to stop methadone treatment altogether (El-Bassel, 2022; Krawczyk 2021). 37,51 These experiences described align with long-running complaints about care provided by OTPs among methadone patients. 14 In designing its new take-home rules, SAMHSA could help address these issues, such as allowing patients to appeal an OTP's decision around take-homes or otherwise request a second opinion.…”
Section: Alternatives and Their Implicationsmentioning
confidence: 68%
See 1 more Smart Citation
“…40,42 The review shows that, as a result of such frustrations, some individuals felt they had to self-manage withdrawal or reported that they wished to stop methadone treatment altogether (El-Bassel, 2022; Krawczyk 2021). 37,51 These experiences described align with long-running complaints about care provided by OTPs among methadone patients. 14 In designing its new take-home rules, SAMHSA could help address these issues, such as allowing patients to appeal an OTP's decision around take-homes or otherwise request a second opinion.…”
Section: Alternatives and Their Implicationsmentioning
confidence: 68%
“…The review reveals that, in the context of pandemic flexibilities, patients often viewed their lack of access to take-homes as unjust, discriminatory, burdensome, and expressed concern at being required to come to the clinic daily even in the midst of a pandemic (Krawczyk 2021, Harris, 2021; El-Bassel, 2022). 37,40,51 Some patients with ongoing substance use or who lacked housing were frustrated that they were excluded from take-home privileges, and others voiced frustrations about being given increased take-home doses that were subsequently rolled back (Lavender 2021; Suen, 2022; Harris, 2021). 32,38,40 Some were denied additional doses and not believed by staff when their doses had spilled, lost, or were stolen from them (Nobles, 2021; Harris, 2021).…”
Section: Alternatives and Their Implicationsmentioning
confidence: 99%
“…Studies, n (%) Description Reasons mentioned [19][20][21]23,25,[28][29][30][31]33,35,[37][38][39]42,45,49,[52][53][54][55][56]60,65,72,73] 26 (43) The anonymous nature of Reddit enables a more candid and open discussion of stigmatized topics.…”
Section: Referencesmentioning
confidence: 99%
“…Anonymous data [18,19,[21][22][23][26][27][28][29][30][31]33,34,38,45,55,57,60,61,65,[72][73][74][75] 24 (40) Reddit is one of the most popular social networking sites.…”
Section: Referencesmentioning
confidence: 99%
“…Additionally, pre-existing imaging data can be used to identify neural features, such as reduction in subcortical integrity, associated with OUD [77]. Patterns and motives of use can even be extracted from social media [78][79][80]. One study identified comments and conversations on suicide among opioid users on Instagram, representing a key health risk factor for OUD on a platform heavily utilized by young adults [80].…”
Section: Population-based Cohortsmentioning
confidence: 99%